Study of terminal ileum findings during total colonoscopy - Zarzouri, Thaer Omar; Madi, Maher; Hammad, Ismael (Journal of medical and pharmaceutical sciences, 2022)
This study aimed at determine the diagnostic value of terminal ileoscopy according to indications for colonoscopy. In addition to, evaluating the duration of the procedure and the rate of success. The Methods An observational descriptive study was conducted for the period of one year (January2020 -January2021) at Tishreen University Hospital in Lattakia-Syria. The study included 198 patients referred for colonoscopy due to various indications.Results: The median age was 53 years, the most frequent age group was 40-60 years (42.9%), followed by the group ≤ 60 (32.8%). Males represented 58.6 % of the patients, and abdominal pain was the most frequent indication for colonoscopy. The success rate of terminal ileal intubation was 83.8% with a mean duration of the procedure 2.15±1.6 m. Abnormal macroscopic findings were found in 23 patients (13.9%) and ulceration was the most frequent feature (4.5%). Significant pathological findings were present in 11 cases (47.8%), and included Crohn's disease (10 cases) and infectious colitis with Yersinia (1 case). The diagnostic yield was 5.5% in all ileoscopies, which was significant in patients with weight loss (20%) and right iliac fossa pain (16.7%).Conclusion: Our study findings demonstrated high percentage of ileal intubation success with variable diagnostic yield according to the indications of colonoscopy.
Keywords: terminal ileoscopy; colonoscopy